Structure of Human Adenovirus - Nemerow, Glen R. (2012)
A detailed structural analysis of the entire human adenovirus capsid has been stymied by the complexity and size of this 150 MDa macromolecular complex. Over the past 10 years, the steady improvements in viral genome manipulation concomitant with advances in crystallographic techniques and data processing software has allowed structure determination of this virus by X-ray diffraction at 3.5 Å resolution. The virus structure revealed the location, folds, and interactions of major and minor (cement proteins) on the inner and outer capsid surface. This new structural information sheds further light on the process of adenovirus capsid assembly and virus-host cell interactions.